Determination of Required Energy Action at Formation of Asphalt Concrete Mixture - B. M. Khroustalev (Izvestiâ Vysših Učebnyh Zavedenij i Ènergetičeskih ob Edinennij SNG. Ènergetika, 2009)
A problem pertaining to determination of the concentrated exergy of the asphalt concrete mixture is considered in the paper. The paper shows the possibility to use the concentrated exergy of the asphalt concrete mixture for qualitative energy evaluation of mixing processes.